Proving Geobacter biofilm connectivity with confocal Raman microscopy - Robuschi, Luciana (2016)
We report here an . in-vivo, non-invasive, depth profiling study on an electrically-active biofilm by Confocal Raman Microscopy. Films based on . Geobacter sulfurreducens bacteria were grown onto an indium tin oxide (ITO) conducting glass, where the ITO piece plays a double role: it acts as a supporting polarized electrode for the bacteria population but also as a transparent window that gives direct access to the biofilm body. A confocal Raman microscope was used to examine the biofilm redox state at increasing distances from the ITO surface, upon variable polarization and under the presence or not of a chemical electron donor or acceptor. Resonant Raman effect allowed to selectively probe the redox response of biofilm cytochromes to the applied potential and chemicals, revealing internal connectivity details of the bacterial population. Full methodological details for this application case are given, while the importance of confocal Raman for the analysis of biological or electrochemically active systems in non-invasive way is highlighted.